2019
DOI: 10.3389/fphar.2019.00854
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms and Adverse Events on Unbound Imatinib and Its Active Metabolite Concentration in Patients With Gastrointestinal Stromal Tumors

Abstract: Imatinib is a first-line drug for the treatment of gastrointestinal stromal tumors (GIST). This study aims to investigate the influence of different kinds of protein concentrations and genetic polymorphisms of metabolizing enzymes and drug transporters on unbound imatinib and its active metabolite N-desmethyl-imatinib concentration, as well as the relationship between adverse drug reactions (ADRs) and drug concentration. A total of 62 Chinese patients with GIST were genotyped for five single nucleotide polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Asian patients with gastrointestinal stromal tumors (GISTs) carrying the T allele at NR1L2 rs3814055 (C > T) exhibited lower steady-state imatinib dose-adjusted plasma concentrations than patients with the wild type (CC), while in the same study patients carrying the mutant T allele at NR1L2 rs3814055 (C > T) showed significantly lower incidence rate of continuous edema, an adverse effect of imatinib [61]. These results are in agreement with the results from Yi Qian et al where patients with the TT genotype of NR1I2 rs3814055 (C > T) were described to have lower unbound imatinib dose-adjusted concentration [62].…”
Section: Gastrointestinal Cancersupporting
confidence: 88%
“…Asian patients with gastrointestinal stromal tumors (GISTs) carrying the T allele at NR1L2 rs3814055 (C > T) exhibited lower steady-state imatinib dose-adjusted plasma concentrations than patients with the wild type (CC), while in the same study patients carrying the mutant T allele at NR1L2 rs3814055 (C > T) showed significantly lower incidence rate of continuous edema, an adverse effect of imatinib [61]. These results are in agreement with the results from Yi Qian et al where patients with the TT genotype of NR1I2 rs3814055 (C > T) were described to have lower unbound imatinib dose-adjusted concentration [62].…”
Section: Gastrointestinal Cancersupporting
confidence: 88%
“…Unbound and bound VRC of all plasma samples from patients and in vitro samples were separated using rapid equilibrium dialysis (RED, Thermo Fisher Scientific, USA) (Qian et al, 2019). In brief, unbound VRC was separated from plasma in a 96-well plate with a semipermeable membrane through which only unbound drug can permeate.…”
Section: Unbound Vrc Separationmentioning
confidence: 99%
“…12 The total and unbound imatinib concentrations in patients with gastrointestinal stromal tumors correlated significantly with ADRs. 13,14 Brake 15 assessed the effect of malnutrition on the steady-state pharmacokinetics of total and proteinunbound rifampin in Indonesian subjects. The large interindividual variability in the free fraction of rifampin suggests that protein-unbound rather than total rifampin concentrations should preferably be used to study exposure-response relationships.…”
Section: Introductionmentioning
confidence: 99%